The Role of minorities in freedom struggle - Engineer, Asghar Ali, 1939-2013.; Institute of Islamic Studies (Mumbai, India) (Delhi : Ajanta Publications : Distributor, Ajanta Books International, 1986)
In the Indian context; comprises papers presented at a seminar organized by the Institute of Islamic Studies in Bombay, 1986.
Keywords: Minorities -- Political activity -- India -- Congresses; Muslims -- Political activity -- India -- Congresses; Nationalism -- India -- History -- Congresses; India -- Politics and government -- 19th century -- Congresses; India -- Politics and government -- 20th century -- Congresses